Analisis Pendapatan Usahatani Sawi Pola Kemitraan dan Non Mitra di Kecamatan Megamendung Kabupaten Bogor Jawa Barat - Annisa Fitri; Harianto Harianto; Ratna Winandi Asmarantaka (Politeknik Negeri Lampung, 2018)
Partnership is one of the institutions that plays an important role in agricultural development in Indonesia. Contracts in partnerships result in differences in production, productivity, and cultivation techniques. Farmers who have not been able to allocate optimally production factors in their farming production processes will influence the production costs and farmers' income. This study aims to identify factors that influence farmers participating in partnerships, the effect of partnerships on the efficiency of mustard farming, and the factors that influence the inefficiency of mustard farming. This study uses cross section data from 70 samples of mustard farmers, consisting of 35 partner farmers and 35 non-partner farmers. The method used is cost analysis and income analysis. The results showed that the average income of partner farmers for cash costs amounted to Rp 20,932,943 and profits at a total cost of Rp 12,828,443. In non-partner farmers, income from cash costs amounted to Rp. 22,118,483 and revenues from total costs amounted to Rp. 14,492,164. Partner farmer income is lower than non-partner farmers. With participation participating partnering to reduce income because of different input and output prices between partner farmers and non-partner farmers.Â Keywords: Partnership, farming income, green mustard